Responses of eggplant (Solanum melongena L. cv MTe 2) towards salinity and development of plant growth enhancer in reducing salt stress - Mohd Arifin, Fateen Khaliessa (2018)
Salinity is the second most widespread soil problem affecting large areas of world cultivated land and is considered as a serious constraint to increase crop production. Seed germination and seedling growth are both important stages in agronomical aspect of crop establishment and both stages are sensitive towards salt stress. Currently, no study has been done regarding salt tolerance of eggplant (Solanum melongena L. var MTe 2). Thus, the present work aimed to compare the effects of different types of salts on seed germination capability, early seedling growth and seed anatomy of the eggplant (S. melongena var. MTe 2) and also to develop liquid formulation to enhance germination and growth of salt-stressed MTe 2 seeds. Ten sterilized Mte 2 seeds were treated with 5 ml of 25, 50, 100, 150 and 200 mM of NaCl, KCl, MgCl2 and MgSO4 in Petri dish with deionized water as control. After 10 days, the germination performance and early seedling growth were evaluated with their parameters, respectively. The ungerminated seed were transferred to distilled water for percent recovery test and also for histological study. Seeds showed highest tolerance and germination performance in KCl followed by NaCl, MgCl2 and MgSO4. The germination percentage, germination rate, relative salt injury rate, seed vigor, salt tolerance, seedling height and biomass were significantly affected by interaction effect between type of salt and concentration of salt. Treatment with 25 mM KCl was found to enhance the germination performance and early seedling growth of MTe 2 seeds. The seeds were unable to germinate even at the lowest concentration of MgCl2 and MgSO4. Percent recovery test revealed that while NaCl and KCl imposed an osmotic stress onto MTe 2 seeds, MgCl2 and MgSO4 imposed a specific ion toxicity that affects the germination performance. The histological study further revealed that osmotic stress induced a state of dormancy which prevented the protusion of radicle from the testa while specific ion toxicity disrupted cell membrane integrity, interfered with metabolism of germinating seeds and caused a cell death to seed embryo. In this study, potassium chloride (KCl), potassium nitrate (KNO3) and indole-butyricacid (IBA) were tested for the effectiveness as a liquid enhancer towards salt stressed MTe 2 seeds. MTe 2 seeds were haloprimed with 200 mM NaCl to induce a salt-stress state to the seeds. The seeds were then dried, surface-sterilized and treated with different combinations of KCl, KNO3 and IBA, respectively. After ten days, the germination performance and early seedling growth were evaluated. Results found that the mixture of 25 mM KCl with 6 ppm IBA significantly produced seedlings with the highest seed vigor and seedling length among all other treatments in compared to control. In conclusion, the salt tolerance of eggplant MTe 2 at germination and early growth stages are as follows: NaCl>KCl>MgCl2>MgSO4. The mixture of 25 mM KCl and 6 ppm IBA were found to enhance the germination performance and early seedling growth of saltstressed eggplant MTe 2.